Heart of Cheyenne : A Truth Revealed - Book 3 - Peterson, Tracie (Minneapolis, Minnesota : Bethany House, a division of Baker Publishing Group, 2024)
"Laura Evans returns home from boarding school, navigating the clash between her deep faith and her father's opposing beliefs. But her world shifts when she crosses paths with a devoted preacher, Wilson Porter, who is driven by his mission to aid the Shoshone people. As their bond deepens, their love is challenged by deception and tragedy"--
Keywords: Clergy -- Fiction; Man-woman relationships -- Fiction; Christian fiction; Romance fiction; Novels